'We're all wounded healers': A qualitative study to explore the well‐being and needs of helpline workers supporting survivors of domestic violence and abuse. (27th December 2018) - Taylor, Anna Kathryn; Gregory, Alison; Feder, Gene; Williamson, Emma
Abstract: Domestic violence and abuse (DVA) can include physical, psychological, sexual, emotional or financial abuses, and is a globally widespread problem across all age groups, cultures and socioeconomic groups. Alongside the impacts of DVA experienced by survivors, there is a growing recognition that other people, who form the support network of survivors, may also be affected by the situation. Domestic violence organisations such as helplines are important third sector services supporting survivors. However, there has been little research into the impact on those providing the support. This qualitative study of domestic violence helpline workers explored their needs and well‐being. We used qualitative methodology, conducting interviews with staff recruited from a selection of different helplines who all undertook direct client‐focused work. The interviews used a semi‐structured format and followed a topic guide covering the training received before commencing work, self‐care strategies, the impact of work on their daily life and support offered by their employer. Ten helpline staff were interviewed, all female. Following analysis of the qualitative data, a number of themes emerged. Participants disclosed numerous ways in which their work challenged their well‐being, including burnout, impact on personal relationships, and lack of training and support at work. Participants used some self‐care strategies in order to "switch off" from work, but they also wanted clinical supervision to support them with the difficulties they experienced at work. This study suggests that helpline staff should receive more education about trauma triggers, and ongoing support to reduce the impact on their home and social life, thus improving mental well‐being and job satisfaction. This work begins the debate on the well‐being needs of frontline helpline workers, and whether better meeting these needs can facilitate the provision of better support.